Budaya Organisasi Dalam Menciptakan Lingkungan Kerja yang Inklusif dan Kolaboratif - Azraqi, Muhammad Willy; Hasibuan, Wildan Ansori; Ramadhan, Ogie; Ujung, Irsyadi; Hasibuan, Rachmad Maulana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
An inclusive and collaborative organizational culture is a key element in improving organizational performance and creating a healthy and productive work environment. Organizations that have an inclusive culture can increase creativity, innovation, and engagement of employees from various backgrounds. This article reviews the concept of organizational culture, factors that influence cultural inclusion, and challenges and barriers in building it. In addition, this article also discusses the evaluation methods used to measure the success of an inclusive and collaborative culture in an organization. The research method used is a literature study that examines various theories and practices related to organizational culture, motivation, and the implementation of inclusive strategies in the work environment. The results of this study indicate that an inclusive and collaborative organizational culture can be achieved through policies that support diversity, open communication, and training that makes employees aware of the importance of inclusivity. The main challenges faced are conscious and unconscious bias and resistance to change in established cultures in the organization.